2003
DOI: 10.1038/sj.ejcn.1601627
|View full text |Cite
|
Sign up to set email alerts
|

Spanish children's diet: compliance with nutrient and food intake guidelines

Abstract: Objective: To compare the diet of Spanish children against the nutrient and food intake guidelines. To calculate an index of overall diet quality and check its validity against nutrient intake. Design and setting: Cross-sectional study in four cities in Spain, where information on food and nutrient intake was obtained from schoolchildren through a food frequency questionnaire. Participants: The sample included 1112 children (overall response rate of 85%) attending public and private schools and aged 6-7 y. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
36
6
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 31 publications
7
36
6
4
Order By: Relevance
“…Moreover, the mean value of the HEI score was almost 61. This finding is partially in agreement with those detected in other similar studies conducted in the United States of America and Spain (Batsiotis et al, 2002;Royo-Bordonada et al, 2003;Feskanich et al, 2004;Knol Batsiotis et al (2002) reported that the mean value of the HEI score was 66 for children aged 7-10 years, 61.4 and 60.8 for females and males aged 11-14 years, respectively . A little higher HEI score was found in a study carried out among the US children aged 6-11 years (that is, the HEI mean score ranged between 63.2 and 69.9) and in lowincome US children aged 4-8 years (that is, the HEI mean score was 65.8 for light eaters and 69.6 for substituters) (Knol et al, 2005;LaRowe et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, the mean value of the HEI score was almost 61. This finding is partially in agreement with those detected in other similar studies conducted in the United States of America and Spain (Batsiotis et al, 2002;Royo-Bordonada et al, 2003;Feskanich et al, 2004;Knol Batsiotis et al (2002) reported that the mean value of the HEI score was 66 for children aged 7-10 years, 61.4 and 60.8 for females and males aged 11-14 years, respectively . A little higher HEI score was found in a study carried out among the US children aged 6-11 years (that is, the HEI mean score ranged between 63.2 and 69.9) and in lowincome US children aged 4-8 years (that is, the HEI mean score was 65.8 for light eaters and 69.6 for substituters) (Knol et al, 2005;LaRowe et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…The few existing studies dealing with dietary fibre intake in infants, children and adolescents from industrialized countries reported intakes below the respective reference used (Nicklas et al, 1995b;Hampl et al, 1998;Decarli et al, 2000;Royo-Bordonada et al, 2003). There is particular lack of data concerning possible long-term changes in dietary habits, especially in children and adolescents of Western industrialized countries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diet of European (pre-school) children is found to be poor as many children do not reach the dietary guidelines (3)(4)(5)(6) . Nevertheless, comparison between countries and different studies is difficult because of the variety of measurement methods used to asses dietary status in pre-schoolers.…”
mentioning
confidence: 99%
“…Also, little is still known about the relationship between overweight and diet quality in preschoolers. Unhealthy food choices can lead to overweight or obesity, so a difference in diet quality could be expected according to weight status, with pre-school children with overweight or obesity having lower scores than pre-schoolers with a normal weight (5,12,18,19) . In addition, an interaction between gender, SES and overweight can be expected.…”
mentioning
confidence: 99%
See 1 more Smart Citation